GlobaliFusion, The First Worldwide, Holistic, Information & Communication Technologies (ICT) and Big Data Aggregation Approach to Social Media Marketing - Greg Sand; Leonidas Tsitouras; George Dimitrakopoulos; Vassilis Chatzigiannakis (Institute of Economic Research (IER), 2015)
The internet and Social Media have been playing a vital role in almost everyone's communication and interactions. The same holds true for a company's two-way communication with its consumers. This tremendous flow of information can drastically increase any company's exposure to its consumers and shoppers. Consequently, it can decisively affect consumers' opinion about products and services. Molloy College in Rockville Centre, New York is the home of GiF, the first worldwide, holistic ICT-based approach to managing the Big Data issue in Social Media Marketing. GlobaliFusion (GiF) aims at bringing together entrepreneurs and companies of all sizes with their consumers by aggregating insights from Social Media and online publications in order to translate them into return-on-investment (ROI) positive marketing strategies and to accelerate their growth, applying technologically innovative and efficient marketing practices. Over the last five years there has been a tremendous shift of investments by marketing departments of major corporations, focusing on Social Media and digital marketing solutions versus traditional media. Despite the abundance of Social Media marketing solutions, there is no concrete framework on how to actually listen to people interacting in Social Media and to use these insights to perform and monitor Integrated Marketing campaigns. Furthermore, monitoring Social Media campaigns' impact on public opinion and decisions through Social Media channels, and assisting companies accelerate their growth accordingly with novel integrated tools and strategies has been an unexplored field. GiF is striving to be established as the global leading platform for increasing the intelligence of companies through social media management and through a group of innovative ICT-based solutions for realizing ROI positive business strategies and tactics.
Keywords: M31; 330; Social Media Marketing; Information and Communication Technologies (ICT); Big Data; Opinion Mining (also known as Sentiment Classification); Augmented Reality (AR)